Severe Tropical Malaria with Acute Kidney Injury: A Case in a Remote Area - Prayoga Adinawer Sirait (PT Kalbe Farma Tbk., 2024)
Background: Malaria remains a major health problem in Indonesia; P. falciparum is responsible for the majority of severe cases and malaria-related deaths. This report presents a case of severe tropical malaria complicated with acute kidney injury treated in a remote area with limited resources. Case: A 25-year-old male with a 9-day history of fever presented to the emergency department with severe headache, nausea, jaundice, abdominal pain, and hemoglobinuria. Microscopic examination of the blood revealed P. falciparum parasites. Laboratory results also showed anemia and thrombocytopenia, bilirubinuria, proteinuria, elevated liver enzymes, and pre-renal azotemia. The patient received antimalarial treatment (dihidroartemisinin/piperaquine once daily for 3 days and a single dose of primaquine) and supportive therapy. He was discharged in a stable condition on the fifth day of hospitalization. Conclusion: Early detection and management is crucial for the patient’s prognosis.